Implementation of Differentiated Learning as an Effort to Increase Teacher Capacity at SMA Negeri 1 Tibawa - Kobi, Wiwin; Mardin, Herinda; Pratama, M. Iqbal Liayong (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
The aim of this service activity is to increase the understanding of teachers at SMA Negeri 1 Tibawa regarding the implementation of differentiated learning. Differentiated learning is an attempt to adapt the learning process in the classroom to meet the individual learning needs of each student. It is important for differentiated learning to be implemented in schools, especially in schools selected as driving schools, so activities were carried out to increase teacher capacity in terms of implementing differentiated learning through workshop activities which were attended by all teachers from SMA Negeri 1 Tibawa, Gorontalo Province. Tibawa State High School 1 is one of the driving schools which has been running for the last 2 years since 2022. Service activities use lecture, discussion and games methods as well as active participation from the participants. There were 46 participants who took part in this activity, all of whom were teachers from the Tibawa 1 State High School (SMA), Gorontalo Regency. This service activity had a very positive impact on the participants who took part in this activity, the participants were very enthusiastic and increased the participants' understanding regarding the implementation of differentiated learning in the classroom.